Ionic current responses of single Au nanoparticles optically confined in a nano-orifice - Hiroki NOMURA; Takao ONO; Kentaro DOI; Satoyuki KAWANO (Mechanical Engineering Journal)
Recently, resistive pulse analysis of single nanoparticles and single biomacromolecules have attracted significant attention. It is known that the volume exclusion in the test section usually causes a decrease in the electrical conductance of ionic current. The amplitude of spike signals and the duration time reflect objects’ characteristics. On the other hand, previously we found that Au nanoparticles (AuNPs) irradiated with near-infrared light showed conductive pulses when the particles passed through the nano-orifice, although a reason why the electrical conductance increased by the light has not yet been clarified. In this study, we investigate the ionic current response to the transport of AuNPs that are confined in a nano-orifice in applied electric fields. The relationship between the current responses induced by AuNPs and near-infrared light irradiation is discussed by classifying the transport modes. It is found that the irradiation of AuNPs is inevitable for the conductive pulses, and on the other hand, the resistive pulses are observed only when the light is turned off. The amplitude of conductive pulse of AuNP with a diameter of 200 nm attains more than 5% of the base current level that is much higher than that of resistive pulses caused by the volume exclusion that is actually at most 1% or less. It has been suggested that conductive pulse analysis has the potential to open the door to novel single particle analysis methods.